Commanding excellence : inspiring purpose, passion, and ingenuity through leadership that matters - Morton, Gary (Greenleaf Book Group Press, 2017)
"Truly engaging people is not about commanding them to do something; it is about getting them to command themselves to do it. West Point distinguished graduate Gary Morton knows how to deliver exceptional results while doing just that. As a platoon leader and tank commander in Army Task Force 4-68 and, later, as a young vice president at medical device manufacturer Stryker, Morton learned under two legendary leaders who, despite different styles, followed nearly the same steps to achieve results most considered unattainable"-- Amazon.com.